Digital ulcers in systemic sclerosis : A retrospective heath service study analysing treatment with bosentan and other vasoactive therapies - Riemekasten, G.; Beissert, S.; Distler, Jörg; Kreuter, A.; Mueller-Ladner, U. (Zeitschrift für Rheumatologie, 2016)
Digital ulcers (DU) affect up to 60 % of patients with systemic sclerosis (SSc) and have a considerable impact on quality of life and morbidity. It is unclear to what extent authorised medicines are used, and if therapy guidelines are implemented in everyday practice.This retrospective health care study examined current standards of treatment for therapy and prevention of SSc-associated DU in an online survey with 83 physicians. Additionally, data from 161 case studies of SSc patients with DU were analysed, and the effect of DU treatment on the course of the disease determined.For treatment and prevention of active DU, physicians predominantly indicated topical therapies, calcium channel blockers, iloprost and endothelin receptor antagonists. According to the case studies, 90 % of episodes with acute DU were treated with bosentan and iloprost in mono- or combination therapy. Preventive treatment was only administered during 50 % of episodes without DU, even after three or more phases with active DU. For the prevention of new DU, bosentan was used in mono- or combination therapy in 57 % of episodes without DU. Bosentan therapy during prevention shortened the following acute phase by 32 %. Additionally, continuous treatment with bosentan in acute and prevention phases reduced the duration of the following acute phase and increased the time to onset of new DU by 16 %. Moreover, bosentan stabilised the number of new DU.In summary, these data confirm the efficacy of bosentan in preventing new DU when used in DU-free episodes and possibly also in phases of acute DU. Therapy recommendations for the treatment of DU are currently not fully implemented. In the future, even more attention should be paid to DU therapy.
EVALuna2:13252